The Influence Of Internal Marketing On Organizational Performance Mediated By Organizational Culture In Micro, Small And Medium-Sized Enterprises - Bakti Setyadi; Sulaiman Helmi; Fitriasuri Fitriasuri (Jurnal Manajemen Industri dan Logistik, 2022)
This study examines how organizational culture functions as a mediator between internal marketing and organizational performance in Micro, Small, and Medium Enterprises in Palembang City. This research uses quantitative methods with a cross-sectional survey. Respondents in this study amounted to 42 respondents, with data analyzed using partial least square structural equation modeling (SEM-PLS). The findings in this study that organizational culture functions as a mediator in the influence of internal marketing and organizational performance on small and medium-sized enterprises. So it is important Micro, Small, and Medium Enterprises ses in the city of Palembang to create a conducive organizational culture.